Analisis Kemampuan Pemahaman Konsep Matematis Ditinjau Dari Tipe Kepribadian Keirsey Pada Peserta Didik MTsN Gowa - Yuliany, Nur; Widiastika Suartawa; Ermawati; Eka Damayanti (Alauddin Journal of Mathematics Education, 2025)
This study aims to identify the classification of students’ Keirsey personality types and analyze ninth-grade students’ mathematical conceptual understanding at MTsN Gowa based on those personality types. This research was conducted because conceptual understanding is a crucial component in learning mathematics; however, many students still struggle to comprehend mathematical concepts even after receiving instruction. Additionally, previous studies have primarily focused on learning models, materials, or cognitive factors and have not explored the role of psychological characteristics such as Keirsey personality types. Therefore, this research addresses this gap by examining whether students’ conceptual understanding is influenced by their personality tendencies. This study employed a quantitative descriptive method with saturated sampling involving all 74 ninth-grade students. The instruments used were the Keirsey personality questionnaire, a mathematical conceptual understanding test, and documentation. The findings show that the personality classification consists of 19 Guardian, 20 Artisan, 13 Rational, and 22 Idealist students. The level of mathematical conceptual understanding is categorized as moderate with an average score of 67.78, which remains below the minimum mastery criteria. Based on personality types, students with the Rational personality type achieved the highest scores due to their analytical and logical thinking tendencies, which support conceptual reasoning. Meanwhile, Guardian personality type students obtained the lowest scores, which may be due to their preference for structured and procedural learning, making abstract conceptual reasoning more challenging. The contribution of this study lies in offering a new perspective in mathematics education by integrating personality-based differentiation. These findings may serve as a reference for developing adaptive and personalized learning strategies that align with students’ psychological characteristics, potentially improving the effectiveness of mathematics instruction.